Groundnut bulletin - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
Stem and pod rots of groundnuts by V Mehan, C Mayee, T Brenneman and D McDonald 1995 Information Bulletin No 44 23pp ISBN 92 9066 314 6